2007
DOI: 10.1002/jso.20952
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin‐proteasome pathway and enhanced activity of NF‐κB in gastric carcinoma

Abstract: This study demonstrates that the constitutive activation of NF-kappa B is likely due to the activation of ubiquitin-proteasome pathway and NF-kappa B can be used as a prognostic biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…25 Previous studies indicate that ubiquitin expression and 26S proteasome activation are increased in gastric cancer. 26 Moreover, proteasome inhibitors exert potent antiproliferative effects on gastric cancer cells. 18 As a pro-survival mechanism, macroautophagy have been reported to protect tumor cells from the cytotoxic effects of cancer therapy.…”
Section: Macroautophagy and Erk Phosphorylation Counteract The Antiprmentioning
confidence: 99%
“…25 Previous studies indicate that ubiquitin expression and 26S proteasome activation are increased in gastric cancer. 26 Moreover, proteasome inhibitors exert potent antiproliferative effects on gastric cancer cells. 18 As a pro-survival mechanism, macroautophagy have been reported to protect tumor cells from the cytotoxic effects of cancer therapy.…”
Section: Macroautophagy and Erk Phosphorylation Counteract The Antiprmentioning
confidence: 99%
“…Ni et al [15] reported that high activity ubiquitin-proteasome pathway in both patient samples and the BxPC-3 pancreatic cancer cell line was detected, and the status of ubiquitinated gelsolin is related to lymph node metastasis of pancreatic cancer. Wu et al [16] found the abnormal activation of ubiquitin-proteasome pathway accelerated the degradation of I kappa B alpha to increase NF-kappa B expression in gastric carcinoma tissues, which was significantly associated with the increase of lymph node metastasis. Therefore, we thought that RNF180, as a member of E3 ubiquitin ligases, might take part in above molecular events to promote the lymph node metastasis from gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al has found that OLC1 was associated with activation of NF-κB signaling pathway [4]. Constitutive activation of NF-κB was detected in gastric tumors before and is closely intertwined with cancer growth and metastasis [1214]. The activation of NF-κB is an early event during tumorigenesis, which can regulate expression of multiple genes involved in carcinoma formation, progression and invasion thereafter [1517].…”
Section: Discussionmentioning
confidence: 99%